Metabolismo visceral em ovinos: custo energético associado ao nível de consumo e ao metabolismo hepático de compostos nitrogenados - Hentz, Fernanda (2013)
The effect of level of forage intake on blood flow and oxygen consumption (Experiment 1), and mesenteric infusion of ammonium bicarbonate (NH4HCO3), L-alanine or L-arginine on oxygen consumption and net flux of metabolites (Experiment 2) through the splanchnic (portal-drained viscera [PDV] plus liver (ST)) tissues were evaluated in sheep surgically implanted with chronic indwelling catheters into the mesenteric, portal and hepatic veins. In both experiments, blood flow was estimated by downstream dilution of p-aminohippurate. In experiment 1, three adult male Polwarth wethers (42±4.4 kg body weight (BW)), housed in metabolism cages and offered Tifton (Cynodon sp.) hay were used in a 3 x 3 Latin Square design. Treatments consisted of hay allowances of 7, 14 or 21 g dry matter (DM)/kg BW/day, offered in four equal daily meals, every 6 h. Blood flow across PDV was linearly (P<0.05) related to OM intake, whereas the hepatic-arterial and total ST blood flow were no affected. Oxygen expenditure by PDV was directly (P<0.05) related to OM intake, while oxygen consumption by the liver was not affected. Oxygen expenditure was linearly (P<0.05) related to blood flow across tissues for PDV, liver and total ST. The proportion of metabolizable energy (ME) intake spent as heat by PDV and total ST reduced when ME intake increased. In addition, this reduction occurred in a curvilinear manner as the difference between PDV and ST heat production reduced at increased ME intake. In experiment 2, four multicatheterized Polwarth wethers (40 ± 3.8 kg BW) fed 14 g DM of oat (Avena sativa) plus ryegrass (Lolium multiflorum Lam) hay/kg BW/day of Tifton hay were used in a 4 x 4 Latin Square design. Treatments were mesenteric vein infusion of 500 μL/min of saline solution (control) or a solution containing NH4HCO3, L-alanine or L-arginine. The net flux of glucose and urea through PDV and ST were not affected by treatments. Portal appearance and liver removal of N-NH3 were higher (P<0.05) with the NH4HCO3 infusion. The PDV and ST net flux of oxygen were not affected by treatments, whereas the hepatic oxygen consumption was higher in control treatment (P<0.05). The hypothesis that ureagenesis and/or gluconeogenesis increases hepatic energy spenditure was not observed in the present study. Methodological aspects are included in results discussion.